ISOLASI DAN IDENTIFIKASI SENYAWA GOLONGAN TRITERPENOID DARI EKSTRAK n- EKSANA DAUN KEPUH (Sterculia foetida L.) SERTA UJI AKTIVITAS ANTIRADIKAL BEBAS - I. A. R. Astiti Asih; I W. G. Gunawan; N. M. Desi Ariani (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2010)
Kepuh leaves can be used as traditional medicine to cure various diseases. Maseration of ± 1000 g drypowder of Kepuh leaves with n-hexane as the solvent resulted in 2,10 g n-hexane concentrated extract. Separation ofthis extract with column chromatography gained two yellow amorphous crystal isolates of F3.1 and F3.2 with 0,0195 gand 0,0032 g in weight, respectively.The result of phytochemical test of isolate F3.1 with Liebermann-Burchard reagent showed that the isolatepositively contained triterpenoid. Identification of isolate F3.1 with spectrophotometer UV-Vis showed one broadpeak at 265 nm. The transition occured probably was n *, that was caused by C=O chromophor. Infraredspectrum showed characteristic groups of OH at 3294,42 cm-1, aliphatic CH at 2924,09 cm-1 and 2854,65 cm-1, C=Oat 1743,65 cm-1, bending CH2 and bending CH3 at 1458,18 cm-1 and 1381,03 cm-1 and alcoholic CO at 1172,72 cm-1.Free antiradical activity test against isolate F3.1 was carried out by spectroscopy UV-Vis method. Isolate F3.1 hadcharacteristic as a free antiradical with DPPH damping percentage at the 5th minute was 85,33% and at the 60thminute was 88,52%.According to phytochemical tests and spectrophotometry analysis, isolates from kepuh leaves was expectedto contain true triterpenoid group compounds with free antiradical activity OH group, aliphatic CH, C=O andalcoholic C-O as the functional groups.